MATERNAL MORTALITY IN GROBOGAN DURING COVID-19 PANDEMIC 2020-2021 - Nurhanifah Hamdah; Mondastry Korib Sudaryo (Universitas Airlangga, 2022)
Background: Maternal mortality is one of the health statuses that is considered global. Central Java Province has the highest maternal mortality rate in Indonesia, and one of the regencies with a high MMR (Maternal Mortality Rate) is Grobogan. Purpose: This research wants to describe maternal mortality in Grobogan in 2020-2021. In further research, we can determine the relationship between risk factors that cause maternal death and use them to develop program decisions to reduce maternal mortality in Grobogan. Methods: This study used a descriptive-quantitative study using Maternal and Infant Mortality data from the Health Office of Grobogan in 2020-2021 and analyzed averages and proportions.Results: This study showed that 103 mothers died, 69% mothers at the age of 20-35 years, 46.60% mothers had Junior High School, 8% were in the Purwodadi 2 area, 73% with gestational age >28 weeks, 52% had 2-3 parity, 87.38% of mothers never abortion, 57% of mothers died during the puerperium, and 39% caused by being infected of COVID-19. Conclusion: Maternal mortality in Grobogan Regency during the 2020-2021 COVID-19 pandemic, most of the causes of death were due to COVID-19 infection, which mainly occurred in mothers aged 20-35 years, last educated at junior high school, at gestational age >28 weeks, parity 2-3, more common in mothers who have never had a history of abortion, and is currently experiencing the puerperium. This maternal death occurred in 28 of the 30 Puskesmas in Grobogan.